2021
DOI: 10.3390/ijerph182111632
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle Medicine Reimbursement: A Proposal for Policy Priorities Informed by a Cross-Sectional Survey of Lifestyle Medicine Practitioners

Abstract: Lifestyle medicine (LM) is a rapidly emerging clinical discipline that focuses on intensive therapeutic lifestyle changes to treat chronic disease, often producing dramatic health benefits. In spite of these well-documented benefits of LM approaches to provide evidence-based care that follows current clinical guidelines, LM practitioners have found reimbursement challenging. The objectives of this paper are to present the results of a cross-sectional survey of LM practitioners regarding lifestyle medicine reim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…10,13,14,24,49,50 Specific to this sample, our previous analysis of this same survey data indicates that 55% of LM practitioners reported frustration at not being able to receive reimbursement for utilizing LM in their practice, as well a lack of support for LM practice from colleagues and administrators. 51 The results of this analysis suggest that the team approach of LM, incorporating dietitians, coaches, exercise physiologists, health educators and others, 52-55 may address feelings of isolation within an ineffective system that respondents in this survey describe as rewarding volume over value. 12,46…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…10,13,14,24,49,50 Specific to this sample, our previous analysis of this same survey data indicates that 55% of LM practitioners reported frustration at not being able to receive reimbursement for utilizing LM in their practice, as well a lack of support for LM practice from colleagues and administrators. 51 The results of this analysis suggest that the team approach of LM, incorporating dietitians, coaches, exercise physiologists, health educators and others, 52-55 may address feelings of isolation within an ineffective system that respondents in this survey describe as rewarding volume over value. 12,46…”
Section: Discussionmentioning
confidence: 94%
“…Additionally, a previous analysis of the survey data presented here found that LM treatment is poorly aligned with current reimbursement pathways. 25 Thus, while some LM practitioners exclusively practice LM, others incorporate LM into their practice to varying degrees. Those able to integrate a greater degree of LM bring more health behavior education and behavior change into their patient encounters, which may occur in the form of one-on-one counseling during an appointment, referral to a dietitian or health coach, or deployment of shared medical appointments (SMAs) for health education.…”
mentioning
confidence: 99%
“…This survey identified reimbursement challenges, including those related to spending more time with patients and payment for the extended care team, as primary obstacles to providing LM services. 91…”
Section: Discussionmentioning
confidence: 99%
“…This assessment aligns with survey results of LM practitioners demonstrating that 59% of respondents reported difficulty achieving sufficient reimbursement from SMAs due to the unpredictability of adequately filling the group visit during normal operating hours of operation and the challenge of obtaining compensation for services provided in non-healthcare community settings, which despite being more convenient for patients lack an NPI number for reimbursement. 91 Some clinicians successfully provide LM services in the FFS model using standard evaluation and management billing codes (99202-99215), chronic care management (CCM) and remote patient monitoring (RPM) codes and a multidisciplinary care team utilizing several billable provider types (physician, NP, PA, RDN, PT/OT, licensed behavioral counselor), including SMAs. 90,92 However, alternative payment models that adequately reimburse the time-intensive, comprehensive approach to supporting health behavior change that is necessary to achieve an optimal therapeutic dose leading to improve clinical outcomes are desperately needed to accelerate the integration of LM into primary care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation